Optimalisasi Produksi Melalui Pelatihan Penggunaan dan Pemeliharaan Mesin Sablon - Hery Riyanto; Zainudin hasan; Afrizal; Ida Farida; Ardansyah (Pusat Studi Teknologi Informasi Fakultas Ilmu Komputer Universitas Bandar Lampung, 2025)
Training on the use and maintenance of screen printing machines for UMKM Komunitas Jumat Berkah in Adijaya Village, Central Lampung Regency, aims to improve the technical skills and production efficiency of small business actors in the screen printing industry. This activity is carried out to overcome common problems that are often faced, such as inconsistent product quality, high machine repair costs, and low knowledge about choosing the right materials and inks. The training methods include theoretical explanations, direct demonstrations, independent practice, and machine maintenance sessions. The results of the training showed a significant increase in participants' skills in operating and maintaining screen printing machines, which has an impact on improving print quality and production efficiency. Participants also gained a better understanding of how to choose the right materials and inks for various products, resulting in higher quality and competitive products in the market. This training has a positive impact on increasing the productivity and competitiveness of UMKM in Adijaya Village. For the sustainability of the program, further training and government support in access to equipment and funding are recommended.